Collection of Wound Exudate From Human Digit Tip Amputations Does Not Impair Regenerative Healing: A Randomized Trial. Issue 41 (October 2015) - Kisch, Tobias; Klemens, Julia Maria; Hofmann, Katharina; Liodaki, Eirini; Gierloff, Matthias; Moellmeier, Dirk; Stang, Felix; Mailaender, Peter; Habermann, Jens; Brandenburger, Matthias
Abstract : Abstract: The regrowth of amputated digit tips represents a unique regenerative healing in mammals with subcutaneous volume regrowth, restoration of dactylogram, and suppression of scar formation. Although factor analysis in amphibians and even in mice is easy to obtain, safety of harvesting biomaterial from human digit tip amputations for analysis has not yet been described. The aim of this study was to evaluate if recovering wound exudate does hamper clinical outcome or influence microbiologic or inflammation status. A predefined cohort of 18 patients with fresh digit tip amputations was randomly assigned to receive standard therapy (debridement, occlusive dressing) with (n = 9) or without (n = 9) collection of the whole wound exudate in every dressing change. Primary endpoint (lengthening) and secondary endpoints (regeneration of dactylogram, nail bed and bone healing, time to complete wound closure, scar formation, 2-point discrimination, microbiologic analysis, inflammatory factors interleukin (IL)-1α, tumor necrosis factor-α, IL-4, and IL-6) were determined by an independent, blinded observer. Patients' characteristics showed no significant differences between the groups. All patients completed the study to the end of 3 months follow-up. Exudate collection did not influence primary and secondary endpoints. Furthermore, positive microbiologic findings as well as pus- and necrosis-like appearance neither impaired tissue restoration nor influenced inflammatory factor release. Here, the authors developed an easy and safe protocol for harvesting wound exudate from human digit tip amputations. For the first time, it was shown that harvesting does not impair regenerative healing. Using this method, further studies can be conducted to analyze regeneration associated factors in the human digit tip. DRKS.de Identifier: DRKS00006882 (UTN: U1111-1166-5723).